Benefit-cost assessment of truck climbing lanes: a case study of I-80 in Wyoming. Issue 2 (7th February 2022) - Haq, Muhammad Tahmidul; Zlatkovic, Milan; Ksaibati, Khaled
ABSTRACT: In combination with challenging geometrical characteristics and environmental conditions, heavy truck traffic along interstate 80 (I-80) in Wyoming often creates operational and safety issues. One of the potentially effective countermeasures that can improve traffic conditions along vertical grade sections is the installation of climbing lanes. This paper presents an operational and safety-based benefit-cost analysis (BCA) for climbing lane installations along I-80 in Wyoming. Seven corridors with proposed climbing lanes were analyzed, and performance measures associated with these segments were collected to evaluate the operational and safety effectiveness. The BCA results indicate that the installation of climbing lanes has a significant potential to improve traffic performances for a 20-year planning horizon, with aggregated benefits significantly outperforming the corresponding costs. The benefit-cost ratio varies between 0.8 and 7.8 where the majority of incurred benefits, up to 98%, comes from safety improvements associated with the new climbing lanes.